Resolving the Battle over Artificial Intelligence in War. Issue 5 (19th September 2019) - Lewis, Larry
Abstract : The US National Defense Strategy – like that of its peer competitors – relies on artificial intelligence (AI) for a military edge in potential conflict as well as a deterrent to such conflict. This reliance on AI raises two challenges: a changing relationship between the Department of Defense (DoD) and industry; and widely held safety concerns about the military use of AI. Recent tensions in that relationship potentially imperil the success of US strategy. In this article, Larry Lewis explains that the use of technology in war is not a new problem, and presents an action plan for improving mutual understanding and dialogue between the DoD and industry. While individual companies should choose their own path, this process should lead to a better shared understanding of risks and ways to better promote safety for the military applications of AI.